Effects of gas flow parameters on droplet spatter features and dynamics during large-scale laser powder bed fusion. (January 2023) - Liu, Zixin; Yang, Yongqiang; Han, Changjun; Zhou, Hanxiang; zhou, Heng; Wang, Meng; Liu, Linqing; Wang, Han; Bai, Yuchao; Wang, Di
Graphical abstract: Highlights: A novel image processing method and spatters feature extraction algorithm were used to obtain the spatter number, the total spatter area, the spattering angle and the spattering velocity of 8 scenarios. The droplet spatter features and dynamics exhibited a strong correlation with the gas flow velocity. The median of the spattering angle under normal melting is around 40° under the SD-A condition and about 60° under the SD-W condition. With the increase of gas velocity, the spattering angle became smaller, the quantity of micro-spatter increased, and the maximum spattering speed of the spatter became higher — up to 12.8 m/s at 2.5 m/s gas velocity. The droplet spatter behavior influenced by gas flow parameters are concluded to three ways: gas flow induced, vapor driven, and melt pool extrusion, presented in backside, upper, and frontside relative to the melt pool. Abstract: The droplet spatters generated by the laser induction directly affect the processing quality of the laser powder bed fusion (LPBF) process, gas parameters are a key factor in this process. In this work, the formation characteristics and dynamic behavior of process-by-products under different gas flow parameters were presented through high-speed imaging. A novel image processing method and spatters feature extraction algorithm were used to obtain the spatter number, the total spatter area, the spattering angle and the spattering velocity of 8 scenarios. With the comparative analysis, scan direction against the gas flow (SD-A) is proved to produce fewer droplet spatters than scan direction with the gas flow (SD-W), and the quantitative relationship between the gas flow parameters and the droplet spatter behavior is established for the first time. The maximum spattering velocity increases to 12.8 m/s as the gas flow velocity rise to 2.5 m/s. Finally, the mechanisms of the droplet spatter behavior influenced by gas flow parameters are discussed. The work provides a theoretically reference for the design and control of gas flow parameters during the large-scale LPBF.